Influence of hybrid air-cooled based strategy on thermal management system performance - Olanrewaju M. Oyewola; Emmanuel T. Idowu; Mebougna L. Drabo (Discover Applied Sciences)
Abstract Existing cooling strategies have shown reasonable performance enhancement in the design of air-cooled battery thermal management systems (BTMSs). However, some of these strategies are accompanied with drawbacks such as increase in pressure drop, poor flow uniformity and poor thermal homogeneity. This study adopts hybrid cooling strategy (HCS), through combination of existing air-cooling strategies to investigate the performance of Z–Type BTMSs. Computational Fluid Dynamics (CFD) method was used to evaluate the performance of the HCSs. The method was validated by comparing Z–Type BTMS numerical simulation results with experimental result from literature. Findings from the study revealed that each strategy provides distinct maximum temperature ( $${T}_{max}$$ T max ), maximum temperature difference ( $${Δ T}_{max}$$ Δ T max ), pressure drop ( $$Δ P$$ Δ P ) and pumping power ( $${P}_{p}$$ P p ) performances for the same operational parameters. For designs with single enhancement, step-like design produced best thermal performance with $${T}_{max}=331.16 K$$ T max = 331.16 K and $${P}_{p}=0.0841 W$$ P p = 0.0841 W . A design with combination of two strategies, also produced reduction in $${T}_{max}$$ T max and $$Δ T_{max}$$ Δ T max by 4.25 K and 8.66 K, respectively, with 2.34 Pa increase in $$Δ P$$ Δ P , when compared with the Z–Type BTMS. Another design with single strategy produced reduction in $${T}_{max}$$ T max and $$Δ T_{max}$$ Δ T max by 4.42 K and 8.01 K, respectively with 3.52 Pa increase in $$Δ P$$ Δ P when compared with the same Z–Type BTMS. This performance shows 3.85% increase in $${T}_{max}$$ T max and with 33.5% reduction in $$Δ P$$ Δ P . Several other designs also exhibited similar performance trend. Hence, this study concludes that adopting hybridization of air-cooled technique in BTMS is a promising technique with wide potential unexplored.